2015
DOI: 10.1149/2.0451602jes
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemistry of Amorphous Si-B Thin Film Electrodes in Li Cells

Abstract: Si1-xBx thin films of 0.071 ≤ x ≤ 0.950 have been synthesized using combinational sputtering. All Si1-xBx film compositions had a highly amorphous structure consisting of amorphous Si and B phases, as characterized by X-ray diffraction. In Li cells, it was found that all of the Si is active and the B is inactive with lithium. Otherwise, the Si1-xBx films have similar characteristics as pure Si film electrodes in Li cells, except with reduced capacity due to the added B. However, shifts in the voltage curves ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…However, a continuous amorphous phase that does not undergo crystallization processes, as it is found in Sn-Si, was identified as the most beneficial alloy anode. [169] A similar principle of adding an electrochemically inactive element to generate a mechanically stable and chemically inert backbone was also investigated by means of thin-film libraries for the following systems: Si-Fe, [170,171] Si-Co, [172] Si-B, [173] Si-M (M = Cr+Ni, Fe, Mn), [174] and Si-Ni. [175] For Si-Co, [172] Si-Fe, Si-Mn, and Si-Cr+Ni thin layer electrodes capacity fading was observed, [174] which was attributed to the formation of inactive silicides due to complete electrochemical inactivity at a concentration of 50 at% Si.…”
Section: Alloy Electrodesmentioning
confidence: 99%
“…However, a continuous amorphous phase that does not undergo crystallization processes, as it is found in Sn-Si, was identified as the most beneficial alloy anode. [169] A similar principle of adding an electrochemically inactive element to generate a mechanically stable and chemically inert backbone was also investigated by means of thin-film libraries for the following systems: Si-Fe, [170,171] Si-Co, [172] Si-B, [173] Si-M (M = Cr+Ni, Fe, Mn), [174] and Si-Ni. [175] For Si-Co, [172] Si-Fe, Si-Mn, and Si-Cr+Ni thin layer electrodes capacity fading was observed, [174] which was attributed to the formation of inactive silicides due to complete electrochemical inactivity at a concentration of 50 at% Si.…”
Section: Alloy Electrodesmentioning
confidence: 99%
“…Obrovac et al systematically investigated the effect of B dopant concentration on electrochemical lithiation/delithiation of an amorphous Si–B thin film prepared by combinatorial sputtering and found that the B is electrochemically inactive with Li. 47 In view of this, it is reasonable that the lithiation/delithiation capacities became smaller for the 12 400 ppm-B-doped Si, where approximately 1 at% of Si atoms are replaced by B atoms. However, the irreversible electrode expansion after the 20th cycle was remarkable for the 12 400 ppm-B-doped Si (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As for the Si−B system, our previous work reported that the Si−B alloys existed at an entirely amorphous state, and no SiB n compounds formed. 31 The thermodynamic data at room temperature of Si−B are very sparse, but it could be inferred that SiB n compounds could be hardly formed in the Si-rich Si− B alloys at room temperature according to the reported thermodynamic properties of the Si−B phase diagram. 37−39 Therefore, TiB 2 should be the first forming alloy phase in the ternary Si−Ti−B, as it has the most negative ΔH′ as shown in the left panel of Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Si–Ti–B ternary alloys are studied using bulk Si, Ti, and B powder as starting materials in this work. Si–B and Si–Ti binary alloys have been studied as lithium-ion anodes. , In the electronic engineering field, boron (B)-doping is a highly effective strategy to improve Si’s conductivity by increasing charge carriers. In addition, the Ti–B compound TiB 2 is an electrical conductor and elastically stiff ceramic .…”
Section: Introductionmentioning
confidence: 99%